Volatilitas Imbal Hasil Saham dan Kaitannya dengan Harga Minyak Dunia (Pendekatan Model ARCH/GARCH dan VAR) - Tiara Kania Ladzuardini (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Volatility generally refers to the amount of uncertainty or risk associated with changes in a security's value. The value of a security can potentially spread over a wider range of values if it has higher volatility. This study aims to analyze the volatility of stock returns and the growth of world oil prices. The stock that the author analyzes in this scientific article is PT Pakuwon Jati Tbk. by using daily time series data from January 2 2019 to December 14 2020. The model used in this study is Autoregressive Conditional Heteroskedasticity (ARCH)/Generalized Autoregressive Conditional Heteroskedasticity (GARCH), to understand clustering volatility behavior, and Vector Autoregression ( VAR) to determine the dynamic behavior between stock returns and world oil price growth. The results of the study show that stock returns and growth in world oil prices have clustering volatility in both variables. The results of the GARCH model, on the LPwon variable, indicate that when the return variable is not influenced by any variable, the tendency for stock returns tends to decrease, in contrast to the lnbrent variable, which tends to always increase.